Reward and Punishment as Drivers of Employee Performance: Reward dan Punishment sebagai Faktor Pendorong Kinerja Karyawan - Rofiyana , Muhamad; Sunarya , Erry; Zafar, Tetty Sufianty (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the era of globalization, the culinary industry faces intense competition, requiring companies to implement effective human resource strategies. Specific Background: PT. Younghyun Star in Sukabumi has adopted a reward and punishment system to align employee behavior with organizational goals. Knowledge Gap: However, inconsistencies in reward distribution and ineffectiveness of punishment measures have raised concerns about their actual influence on employee performance. Aims: This study aims to evaluate how the implementation of reward and punishment systems affects employee performance. Results: Using a quantitative, descriptive design and data from 88 employees analyzed with SPSS v26, the findings reveal that both reward and punishment systems have a positive and significant effect on performance, with punishment showing a stronger influence (t = 5.938) than rewards (t = 2.687). Novelty: This research highlights the imbalance between perceived fairness in incentive allocation and the motivational impact of disciplinary actions, offering a contextual insight into behavioral outcomes in a culinary-sector enterprise. Implications: The study suggests that for such systems to be more effective, companies must ensure transparency and consistency, thereby enhancing employee motivation and operational productivity.Highlight : Reward and punishment systems both significantly improve employee performance. Monetary and non-monetary rewards increase motivation, though rule compliance remains low. Strict punishment enhances work discipline, but overuse may hurt emotional stability. Keywords : Reward System, Punishment System, Employee Performance, Human Resource Management, Motivation Tanya ChatG